Effectiveness of #FeelThePower Campaign Message on the Followers of Azarine Cosmetic’s Instagram Account - Auryn Nathania Soputra; Astri Yogatama; Ido Prijana Hadi (Communication Science Department - Petra Christian University, 2023)
Effectiveness can be interpreted as the result or influence that arises from a communication process, namely attitudes, behavior, and responses from a communicant whether desired or not desired. The purpose of this research is to find out the effectiveness of the #FeelThePower campaign message for Azarine cosmetic Instagram followers which aims to make customers feel the power that comes from Azarine's ingredients and inner strength to stay confident and always give the best for yourself. This campaign is carried out by launching new products and collaborating with Disney Marvel. Measurement of effectiveness is carried out using the AIDA measurement method (Attention, Interest, Desire, Action). Data was collected by distributing questionnaires to 100 respondents using a purposive sampling technique. Based on research results, the message of the #FeelThePower campaign is categorized as effective. Of the four indicators, the attention stage has the highest mean value, which means that the respondent's attention to the campaign message is the highest compared to other indicators.